Integration of Thomas Lickona’s Thought and Bima Local Wisdom in Islamic Character Education for Adolescents - Junaidin; Supriatman, Yan Yan; Sativa, Nurul Ilma Oriza; Safitri, Ratu Alya; Alfahira, Aisyah (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study aims to explore the role of parenting and character education based on Thomas Lickona's theory in shaping the moral identity of adolescents by integrating the local cultural values of the Bima community. The phenomena of globalization, social media, and weakening social control pose various moral challenges for adolescents in Bima City, thus requiring contextual character education strategies. This study uses a qualitative method with a library research approach, which involves a review of Thomas Lickona's main books, 31 scientific articles, and literature related to parenting and the local culture of Bima. Data analysis was conducted through content analysis with a focus on three main aspects: character education based on Lickona's theory (moral knowledge, moral feelings, and moral actions), parenting patterns, and local cultural values such as nggahi rawi pahu, maja labo dahu, and kasama weki. The results showed that democratic parenting accompanied by role modeling, emotional closeness, and internalization of local cultural values can strengthen the formation of moral identity in adolescents. The integration of Lickona's theory with local wisdom not only produces comprehensive character education but is also relevant to the socio-cultural context of the Bima community. This study emphasizes the importance of collaboration between families, schools, and communities in creating a holistic, contextual, and sustainable educational environment to face the challenges of modernization.